Uptake of Cd2+ by Synthesized Zeolite from Thermally Activated Tunisian Kaolinite - Frini-Srasra, N.; Srasra, E. (Asian Journal of Chemistry, 2010)
Thermal activated Tunisian kaolinte (CEC = 10 meq/100 g of calcined clay) was used to synthesize a molecular sieve by hydrothermal treatment in alkaline medium. The obtained zeolite corresponds to the A type. The cation exchange capacity of this new material reaches 340 meq/100g of calcined zeolite. The uptake of Cd2+ on zeolite-A was studied using cation exchange measurement. The effect of pH on the uptake has been reported.